Ribonucleic Acid and Protein Metabolism in Pea Epicotyls : II. Response to Wounding in Aged Tissue - Schuster, Anne M. (1983)
Aged pea Pisum sativum L. var Alaska epicotyl tissue was wounded by excising the apical 10 or 20 millimeters and incubating the excised segments upright in buffer. Wounding induced a very rapid formation of polysomes which was accompanied by minor increases in ribosomes, mRNA, and poly(A) and by a doubling of the in vivo protein synthesizing capacity. This increase in protein synthesis in vivo was matched by a similar increase in polypeptide synthesis in vitro in wheat germ reactions primed by polysomes. However, in vitro reactions primed by total and polysomal RNA from wounded tissue were affected much less. Two-dimensional gel patterns of silver-stained proteins accumulated in vivo were almost unchanged, even after 6 hours of wounding, since only two spots decreased in intensity and none increased. In contrast, two-dimensional gel fluorographs of polypeptides generated in vitro by both total RNA and polysomal RNA showed numerous changes within 3 hours of wounding. Of the more than 200 spots visualized by fluorography, 17 decreased and 26 increased when total RNA from wounded tissue was used; 15 decreased and 10 increased when polysomal RNA was used. Those polypeptides that decreased after wounding were generally of lower molecular weight; those which increased were of higher molecular weight. Although wounding must be affecting transcription insofar as different mRNAs must be present to encode different polypeptides, its major effect appears to be on translation, presumably through formation of ribosomes with greater translational efficiency.